Communities of Practice of the Future in Russian Universities: Fablabs, Centers for Youth Innovative Creativity, Kruzhoks - D. I. Zemtsov (Высшее образование в России)
The purpose of this article is to determine the potential for constructive social change that can reach the communities of technology enthusiasts in Russian universities, and to identify possible directions for such changes. University communities of technology enthusiasts and the sites where they work are chosen as the object of research: fab labs, CMITs, circles. The basic conceptual framework of the research is the theory of fields, which asserts that society is a system of embedded social fields. Social changes in this theory are referred to as the transformation of existing social fields or the emergence of new ones. The term “practice of the future” is first introduced, and understood as a group of people united by common interests in advanced technological and social solutions sharing common activities and knowledge (sharing), but not included in a sustainable social field. The hypothesis of the present study is that communities of practice of the future have the capacity for social change and the directions of such changes can be identified through the analysis of strategies that are consistently applied in these communities. The semi-structured in-depth interviews of leaders and participants of university student technological centers are used as the material for the study. The article concludes that the two most obvious social fields in which communities of technology enthusiasts of Russian universities are capable of producing changes are the field of technological entrepreneurship and the field of educational innovation. In the first of these fields, the strategies of technology enthusiasts (initiative, project orientation, diversity and meritocracy) give advantages over players who do not employ these strategies. In the second field (educational innovation) these strategies can give the direction of changes, bringing together enthusiasts of relevant educational technologies. Social changes of the techno-optimistic type generated by the university communities of technology enthusiasts is not yet directed to a specific social field. However, examples of large-scale country-wide projects show that such a field is beginning to form. It is quite possible that modern university communities of technology enthusiasts are able to generate a social field no less powerful than their predecessors – the movement of technological kruzhoks – at the begining of the 20th century.